DIFFERENCES IN FEAR OF MISSING OUT (FOMO) BEHAVIOR IN EARLY ADULTHOOD IN BASED OF GENDER - Karina Eninta Br Ginting; Yohanes Heri Widodo (Universitas Sanata Dharma, 2025)
This research uses quantitative methods with a comparative research design. The objectives of this study include: 1) Knowing whether there are differences in FoMo behavior in early adulthood based on gender; (2) Knowing how high FoMo behavior is in early adult males; (3) Knowing how high FoMo behavior is in early adult females; (4) Knowing high FoMo behavior items to be proposed as training topic services.This research is aimed at early adults with the age criteria of 18-25 years. The research subjects were 152 early adults consisting of 75 male respondents and 77 female respondents. This study uses the FoMo scale which consists of 50 used items with 4 aspects, namely: 1) Social Needs; 2) Seeking Approval; 3) Emotional; 4) Social Media. This scale has good reliability with a Cronbach's Alpha index of 0.929. Assumption testing produces data that is not normally distributed and is not homogeneous. Because the assumption test was not met, the Mann Whitney non-parametric t-test was used.The results of the study showed that 1) There is no significant difference between male and female FoMO behavior; 2) The FoMO category in early adult male individuals tends to be moderate (45%); 3) The FoMO category in early adult female individuals tends to be low (45%); 4) There are 4 proposed training topics based on items that are categorized high, namely “building healthy social connections in the digital era”, relying on yourself in the midst of a noisy world, “The art of self-control”, and “Choose need or dependence?”.